Meningkatkan Kesadaran Masyarakat tentang Pentingnya Karantina Kelautan dan Perikanan di Provinsi Bengkulu melalui Program Liputan Berita di Kantor Karantina Perikanan BKIPM - Yovi Apridiansyah; Wijaya, Ardi; Putra, Riky Ade; Agustio, Faidillah; Febitri, Nora; Rasyid, Muhammad Soelaiman (JURNAL BESEMAH, 2023)
The news coverage program at the Fisheries Quarantine Office of the Fish Quarantine Center for Quality Control and Safety of Fishery Products (BKIPM) of Bengkulu Province has been developed to increase public awareness about the importance of marine and fisheries quarantine. A news coverage product containing information on marine and fisheries quarantine was successfully produced and distributed via social media and other online platforms. Surveys and interviews before and after program development indicate an increase in public awareness of marine and fisheries quarantine issues. The results and discussion of the news coverage program identified the important role of the media in increasing public awareness of environmental issues, challenges in developing news coverage programs, and the potential for developing news coverage programs at the BKIPM Bengkulu Fisheries Quarantine Office in the future. The conclusions and suggestions from this journal are that the news coverage program at the BKIPM Bengkulu Fisheries Quarantine Office can be an effective effort in increasing public awareness about the importance of marine and fisheries quarantine in Bengkulu Province by involving the role of the media and collaboration with other parties.